Application of platelet-rich plasma therapy combined with 5E rehabilitation nursing mode for patients with knee osteoarthritis (富血小板血浆联合5E康复护理模式在膝骨性关节炎患者中的应用) - AN Linjing (安林静); ZHAO Chen (赵晨); CHANG Yueyuan (常月圆); PAN Yaying (潘亚英); CHEN Yanqi (程艳琪); ZHANG Bing (张兵); CHEN Weinan (陈炜楠); GAO Bei (高蓓); NIU Jing (牛静); ZHANG Ting (张婷) (中西医结合护理)
Objective To explore the clinical effect of platelet-rich plasma therapy (PRP) combined with 5E rehabilitation nursing mode for patients with knee osteoarthritis. Methods Totally 80 patients with knee osteoarthritis admitted to the orthopedics department of the hospital from March 2021 to March 2023 were selected as subjects. They were divided into test group and control group according to ward odd and even numbers, with 40 cases in each group. The control group was treated with PRP injected into knee joint cavity combined with routine exercise guidance. The experimental group was treated with PRP injected into knee joint cavity combined with 5E rehabilitative nursing mode. The effect of intervention at 6 months and 12 months after treatment was observed. Results The Visual Analogue Scale of pain in the experimental group was significantly lower than that of the control group at 6 months and 12 months after treatment(P＜0. 01). The score of Western Ontario and McMaster Universities osteoarthritis index (WOMAC) in the experimental group was significantly higher than that of the control group at 6 months and 12 months after treatment(P＜0. 01). Conclusion Platelet-rich plasma therapy combined with 5E rehabilitation nursing model can effectively relieve pain and improve knee joint function in patients with knee osteoarthritis. (目的 探讨富血小板血浆联合5E康复护理模式在膝骨性关节炎患者中的应用效果。方法 采用便利抽样法抽取2021年3月—2023年3月医院骨外科收治的膝骨关节炎患者80例为研究对象, 按照病房单双号依次分为试验组和对照组, 各40例。对照组采用PRP 注入患者膝关节关节腔内并联合常规运动指导进行治疗, 试验组采用富血小板血浆注入膝关节关节腔内联合5E康复护理模式进行治疗。并观察两组患者的治疗后6个月、12个月的效果。结果 治疗后6个月与12个月时, 试验组VAS评分低于对照组, 差异有统计学意义(P＜0. 01)。治疗后6个月与12个月时, 试验组西安大略和麦克马斯特大学骨关节炎指数(WOMAC)评分低于对照组, 差异有统计学意义(P＜0. 01)。结论 富血小板血浆联合5E康复护理模式能有效缓解膝骨性关节炎患者疼痛, 改善患者膝关节功能。)